STUDY ON THE IMPACT OF SOCIAL MEDIA ON ADOLESCENT IDENTITY FORMATION - Chauhan, Neeraj (International Journal of Research -GRANTHAALAYAH, 2025)
Adolescence is a crucial stage in this formation of identity, and it is usually determined by interactions with relatives, peers, and cultural norms established in the society. However, with the advent of the social media a new dimension has been added to this phenomenon whereby young people have gotten unprecedented opportunities to articulate, discover and affirm themselves. Social media apps like Facebook, Instagram, TikTok, or Snapchat allow young people to present and construct their identities to a global audience, experimenting with different identities and receiving an immediate response of their peers. Even though the social media has the prospect of being the medium of empowerment, it also brings with it complications that make formation of stable and consistent self-identity difficult. The constant pressure to meet the unrealistic standards of beauty, the serious emotional consequences of online bullying, and the difficulties connected to the protection of personal privacy may all have a pernicious impact on the mental state and the overall well-being of the younger generation. This academic paper acknowledges the complex role of social media in adolescent identity formation by pointing out the numerous benefits that it can provide as well as the risks that are posed by its use. The study explore the complex psychological and social consequences of the use of social media platforms. It highlights the need to have a balanced approach to this, which means that young people must be equipped with the tools they need to navigating these virtual spaces responsibly. The goal here is to create an environment where young people may use social media as a positive tool of self-discovery, simultaneously minimizing its harmful effects.